Aid and poverty: Why does aid not address poverty (much)? - Andrew Shepherd; Sylvia Bishop (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Aid is not generally aimed at the poorest people, though most multilateral or bilateral agencies would like to think they get included. However, donors' strategies are generally blind to differentiation among the poor, and have not improved in this respect. The special provisions for the least developed countries, where many of the poorest people live, have not worked well. Aid to conflict-affected countries is itself in crisis. Much greater and more integrated aid is called for in both cases. Middle-income countries are themselves becoming donors, but the poorest populations of these countries have benefited from international partnerships which draw attention to the poorest and help foster innovative policy responses. Equity is far from being a strong principle of aid givers UNICEF is the exceptional agency. The human rights based approach to development, which would give much greater weight to the poorest, in practice languishes at the margins of development, though where this has been taken up in middle-income countries (e.g., India) donors have stood on the sidelines. Explanations of this fairly dismal state of affairs are offered in terms of political economy and organizational and profession incentives. Finally the paper sketches a set of issues which need to be incorporated into the post 2015 framework and its preparation if poverty is to be taken more seriously by donors.
Keywords: F35; F50; F55; D63; I38; 330; aid; poverty; conflict; least developed countries; post-2015; Entwicklungshilfe; Armut; Vierte Welt